2004
DOI: 10.1093/annonc/mdh013
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for central nervous system occurrencein elderly patients with diffuse large-B-cell lymphoma: influenceof rituximab

Abstract: Rituximab did not influence the risk of CNS occurrence, possibly because of low rituximab diffusion. Direct intrathecal administration of rituximab could overcome this problem. We also confirmed that CNS occurrence is related to IPI as well as very poor prognosis of relapses occurring on therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
203
3
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(215 citation statements)
references
References 13 publications
4
203
3
5
Order By: Relevance
“…However, when analysing the patient material with regard to the CNS relapse rate, no difference was recorded between the CHOP and rituximab/CHOP arms (28).…”
Section: Discussionmentioning
confidence: 94%
“…However, when analysing the patient material with regard to the CNS relapse rate, no difference was recorded between the CHOP and rituximab/CHOP arms (28).…”
Section: Discussionmentioning
confidence: 94%
“…The addition of rituximab to standard CHOP-21 appeared to have no influence on CNS recurrences in the landmark GELA trial of R-CHOP versus CHOP, with an overall 5% risk of CNS recurrence reported among elderly patients with DLBCL, regardless of treatment arm. 23 However, when the RICOVER-60 trial compared R-CHOP with CHOP in a dose-dense manner, there were modestly fewer recurrences in the rituximab-treated patients noted on univariate analysis Original Article (6.9% vs 4.1%), although this was not significant on multivariate analysis. A notable observation in both the GELA and RICOVER-60 trials was that CNS recurrences in R-CHOP-treated patients were predominantly parenchymal, not leptomeningeal, as had been reported before the introduction of rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of leptomeningeal disease at diagnosis ranges from 3.7% to 25%, and it is related to several factors, such as the different histological subtypes, the involvement of particular sites of disease (ie, testis, bone marrow, Waldeyer ring, or retroperitoneal masses), and an increased serum lactate dehydrogenase (LDH) level. [1][2][3][4][5][6][7][8][9][10][11] Moreover, the overall incidence of CNS recurrence with or without intrathecal prophylaxis is around 5%. 3,[12][13][14][15] Since the beginning of the acquired immune deficiency syndrome (AIDS) epidemic, a close association between human immunodeficiency virus (HIV) infection and high-grade NHL has been reported.…”
mentioning
confidence: 99%